ANALISIS SISTEM PENGEREMAN PADA MOBIL MITSUBISHI L300 JENIS PICK-UP - Mustofa, Mustofa; Syahrani, Awal (Jurnal MEKANIKAL, 2011)
This research aims to analyze the parameters affecting the approach of analyzing both drum and disc brakes on Mitsubishi L300 vehicle of pick-up type. Supporting data was procured by measuring intensively the car brakes component in the Automotive engineering laboratory of Tadulako University and in the Duty Communication of District in Palu. Result of calculation indicates that rotation drum brake both CW and CCW affects the braking force (F). They are 643 and 2.828 kg, respectively. Associating with disc brakes, the tread of pedal brake influences oil pressure on brakes leading to force brakes on the axle. Permitting pedal force is about 19 kg. To pursue brakes analysis on the vehicle, simulation should be taken.